PEMANFAATAN APCA (APLIKASI CANVA) UNTUK MENINGKATKAN MINAT BELAJAR DAN KREATIVITAS SISWA - Widyastuti, Anita (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
This research aims to determine the use of the Canva application as a learning medium to increase learning interest and creativity in class VI students at SDN 2 Pagutan. This research is Classroom Action Research through the planning, action, observation and reflection stages. The subjects of this research were 8 students. The data collection techniques used were direct observation, questionnaires and documentation. This classroom action research procedure was carried out in two cycles, namely pre-cycle, cycle I, and cycle II. From the results of data analysis, the percentage of students' interest in learning increased from the pre-cycle condition of 62.50% or 5 students were in the low interest in learning category, increased in the first cycle to 75.00% or 6 students were in the category of high interest in learning, and increased in the cycle II where there was no longer any interest in learning from low or medium students but increased to 87.50% or 7 students in the high interest in learning category, and an increase in the category of very high interest in learning by 12.50% or 1 student. The increase in student creativity can also be seen from the pre-cycle results of 37.50% or 3 students falling into the less creative category and increasing in the first cycle to 50.00% or 4 students falling into the quite creative category. Creativity in cycle II also increased to 50.00% or 4 students in the creative category and increased to 37.50% or 3 students in the very creative category. Based on these data, it can be concluded that APCA (Canva application) can increase students' interest in learning and creativity.